PEMANFAATAN METODE AGILE DEVELOPMENT DALAM SISTEM INFORMASI KEPEGAWAIAN DI INSTITUT ASIA MALANG - Akbar, Dzikrullah; Andini, Titania Dwi; Asmoro, Zain Bagus Dwi; Noercholis, Achmad (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
This research was conducted at an educational institution, specifically at the Asia Institute of Technology and Business in Malang (Asia Institute Malang). The aim was to develop an employee information system that was previously manual (paper-based) and supported by a simple data processing application, transforming it into a web-based information system that can be accessed anytime, anywhere. This ensures that requests for approval (such as permission requests and schedule changes) do not have to wait for a long time. In the future, this system will evolve both in terms of platform and overall employee data management. The research employed the Agile Development method, customized to meet user demands for immediate application use. The Agile Development model used was the Scrum model, involving activities such as system requirements analysis, design, code generation, testing, and support.